PHYSICAL INTERPRETATION OF THE REFERENCE FEATURES IN TEXTURAL FRACTOGRAPHY OF FATIGUE FRACTURES - Hynek Lauschmann; Filip Šiška (Acta Metallurgica Slovaca, 2013)
Reference features of a fatigue fracture surface are the reference texture and reference crack growth rate which are unambiguously mutually related. The reference texture is a subset of the image texture in SEM fractographs. It is expected to be common to all fractures caused by loadings in which significant events occur sufficiently regularly and frequently. The ratio of the reference and the conventional crack growth rate called reference factor is a characteristic of a particular loading. Its value may be related to the sequence of successive sizes of the cyclic plastic zone, while the mechanism of the effect of overloads follows the models of Wheeler and Willenborg. Application to a set of nine test specimens from aluminium alloy loaded by three different loading regimes is shown.